Risk analysis related to operations in oil and gas plant : the challenges for quantitative and qualitative analysis - Noor Lyana Azira, Abdul Aziz (2014)
This research is related to the circle of risk management in an oil and gas industry which only discussing the items with regards to risk analysis phase only instead of embedded up to whole of phases in the managing risk. In this industry, there are onshore and offshore sectors. Additionally, the scope of this research is only covering the plant in onshore sites. This research is conducted as there are several flaws or weaknesses in analyzing risks in the onshore plant. These weak points caused the risk analysis done previously seems relatively not effective since there is still accident happened in the plant. Therefore, this research was carried in order to search out what are the challenges that contribute to the existence of those flaws. This research was also done to determine the types of risks that have high possibilities to take place in undesirable future condition as well as investigating the types of risk analysis practiced by the personnel in analyzing these risks. The scope of this research is not over than the states of Pahang and Terengganu in the East Coast region of Malaysia. By referring to the previous academic sources, the term “risk” itself could brings either positive of negative definition. In the nature of risk, there are sequences of risk attitude when dealing with risk. The major types of risk attitude are risk averse, risk neutral and risk acceptance. The sources also discussed on the operations of the oil and gas plant as well as the types of risks identified that related to those operations. The most important parts of the information are the knowledge of the types of techniques used to analyze risk such as FMEA and HAZOP as well as the challenges that have been identified in conducting risk analysis in other industries generally. The type of sampling method used in this research was the simple random sampling which is the most suitable method to choose the targeted samples. By thorough discussions on the findings, there are five major types of risks exist in the onshore oil and gas plant which are fire, explosion, gas and equipment or machinery risks as well as maintenance risk. There are more than one type of risk analysis technique practiced in the plant such as the HAZID, HAZOP, FMEA, fault tree analysis and the HIRARC. Moreover, this research highlighted four specific challenges faced during the risk analysis process like limited of data, optimistic estimating, complex measurement and communication of risks and last but not least interpreting past data to predict or make decision of future risks.